Occupational health aspects of deciduous fruit farm workers in certain areas of the Western Cape exposed to agricultural pesticide spray materials - Barnes, J. M.,Mrs (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc (Epidemiology)) -- University of Stellenbosch, 1995.